2021
DOI: 10.4269/ajtmh.20-1209
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis of Malaria Illness in an Endemic Setting: A Facility-Based Surveillance Study in Malawi

Abstract: In endemic settings where asymptomatic malaria infections are common, malaria infection can complicate fever diagnosis. Factors influencing fever misdiagnosis, including accuracy of malaria rapid diagnostic tests (mRDTs) and the malaria-attributable fraction of fevers (MAF), require further investigation. We conducted facility-based surveillance in Malawi, from January 2012 through December 2013 in settings of high perennial (Chikhwawa), high seasonal (Thoylo), and moderate seasonal (Ndirande) malaria transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…The high malaria prevalence in adults off TS prophylaxis is similar to in children <5 years of age in Malawi [20]. In Malawi, we and others have observed similar rates of malaria infection among young children and adults [29][30][31], although incidence of clinical disease decreases with age [32]. However, unlike young children who suffer from severe morbidity and mortality due to malaria, malaria disease in PWH remains generally uncomplicated and without long-term consequences.…”
Section: Discussionsupporting
confidence: 53%
“…The high malaria prevalence in adults off TS prophylaxis is similar to in children <5 years of age in Malawi [20]. In Malawi, we and others have observed similar rates of malaria infection among young children and adults [29][30][31], although incidence of clinical disease decreases with age [32]. However, unlike young children who suffer from severe morbidity and mortality due to malaria, malaria disease in PWH remains generally uncomplicated and without long-term consequences.…”
Section: Discussionsupporting
confidence: 53%
“…A similar study to ours uncovered a large burden of chikungunya virus infection among Kenyan children [ 29 ]. The high prevalence and force of infection of malaria, in combination with lack of routine surveillance for arboviruses such as DENV or chikungunya virus, contribute towards under-recognition of alternate or concomitant causes for AFI and over-diagnosis of malaria [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although CHIKF has been reported in Malawi’s closest neighboring countries such as Tanzania, Mozambique and Zambia [ 26–28 ], Malawi remains the only country in Central Africa to lack such published data. In addition, a study conducted in Malawi reported that malaria is often over diagnosed in febrile patients [ 29 ]. This may be due to lack of epidemiological data and knowledge gap of other aetiologies of febrile illnesses other than malaria in Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports the results published elsewhere that malaria is no longer a huge public threat but other aetiologies of fevers have emerged that are responsible for high morbidity in Sub-Saharan countries [ 43 ]. The absence of the sero-epidemiological data of other aetiologies of fevers hampers the proper management of patients and is the main reason why many febrile illnesses are over diagnosed as malaria in Malawi [ 29 ]. The detection of CHIKV in this study as an aetiology of febrile illness supports the latter and the need for a continued surveillance of other aetiologies of febrile illnesses such as CHIKV in Malawi.…”
Section: Discussionmentioning
confidence: 99%